Evidence for a nanosize effect on the structural and high performance electrochemical properties of V2O5 obtained via fluorine chemistry. (10th August 2017) - Huo, D.; Contreras, A.; Laïk, B.; Bonnet, P.; Guérin, K.; Muller-Bouvet, D.; Cenac-Morthe, C.; Baddour-Hadjean, R.; Pereira-Ramos, J.-P.
Abstract: In this study, we demonstrate the benefit of an original vanadium pentoxide (V2 O5 ) nanostructuration on the electrochemical performances. This new synthesis way of high purity nanosized V2 O5 consists in a facile fluorination reaction of micro-V2 O5 in aqueous solution followed by a heat-treatment at low temperature (230 °C). Highly porous calisson-like particles with crystallite sizes in the 13–30 nm range are obtained. Remarkably, this nanostructured V2 O5 exhibits outstanding rate capacities and cycling stabilities. This material can deliver reversible capacities of 260 mAh g −1 at 15 mA g −1 (C/10 rate) and 150 mAh g −1 at 300 mA g −1 (2C rate), as well as a stable capacity of 200 mAh g −1 at C rate after 50 cycles. The unique structural features of nano-Lix V2 O5 electrodes are determined over the large Li composition range 0 ≤ x < 2 based on XRD and Raman microspectrometry experiments. We provide evidence that lithiation in nanosized V2 O5 proceeds via solid solution state without domain boundaries: a single phase behavior of the ε'-type whose interlayer distance and unit cell volume linearly increase with x is revealed. This constitutes a disruption of the usual mirco-Lix V2 O5 phase diagram made of the successive appearance of the (α/ε), (ε/δ) and (δ/γ) wide biphasic regions. These limited and reversible structural changes combined with shorter Li diffusion pathways explain the huge improvement in electrochemical performances of nano-V2 O5 . These findings fully elucidate the peculiar voltage profile of nanosized V2 O5 and give a unique insight into the impact of nanostructures in terms of electrochemistry and solid state chemistry.